Models of rotating stars constrained by asteroseismic measurements of red giants. Issue 8 (30th September 2016) - Eggenberger, P.; Lagarde, N.; Miglio, A.; Montalbán, J.; Ekström, S.; Georgy, C.; Salmon, S.; Meynet, G.; Maeder, A.
Abstract: Solar‐like oscillations have now been characterized for a large number of stars, thanks to asteroseismic data obtained recently by space missions. This has led to the determination of the global and internal properties of these stars. In particular, core rotation rates have been obtained for red‐giant stars, which is of prime importance for progress in the modelling of the dynamical processes at work in stellar interiors. In this presentation, we discuss which constraints can be brought by these asteroseismic measurements on stellar models that include rotational effects. Similarly to the solar case, we show that an efficient mechanism is required for the transport of angular momentum in the radiative zones of red giants. The efficiency of this transport process can be determined by asteroseismic observations of red‐giant stars.